Pengaruh Transaksi Digital Banking, Kualitas Aset, dan Aspek Permodalan terhadap Profitabilitas Bank Umum di BEI - Wiranti; Yudiantoro, Deny (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The research aims to test and analyze the effect of Digital Banking Transactions, asset quality, and capital aspects on the profitability of banking companies listed on the Indonesian Stock Exchange for the 2015-2021 period. The population consists of 46 companies and banks listed on the IDX. Meanwhile, purposive sampling selected the sample by specifying six companies’ banks as research objects. The research method uses panel data regression as measured by the e-views 12 prprogramsThe results of the analysis of this study are partially Internet Banking Transactions have a positive and significant effect on ROA; meanwhile, the NPL and CAR variables have a negative and insignificant impact on ROA. Simultaneously, the variables Internet Banking Transaction, NPL, and CAR can influence ROA by 80,2%, and the other 19,8% were influenced by other variables not included in the study.